IMPLEMENTASI PAJAK PENGHASILAN PASAL 25 DI INDONESIA - Tyara Amanda; Dini Vientiany; Salwa Balqis; Surya Dimas (INTERNATIONAL, Journal of Sharia Business Management, 2026)
This study aims to analyze the implementation of Income Tax Article 25 in Indonesia and to identify the challenges encountered in its application. The research employs a descriptive quantitative approach using a library research method, relying on secondary data such as tax regulations, official government reports, and relevant academic literature. The results indicate that the implementation of Income Tax Article 25 has generally been effective in supporting the stability of state revenue through a monthly tax installment mechanism. In addition, the digitalization of the tax system, including e-billing and e-filing, has contributed to improving administrative efficiency and enhancing taxpayers’ formal compliance. However, several challenges remain, including the complexity of installment calculations, reliance on previous year tax data that may not reflect current economic conditions, and the limited understanding of tax regulations among some taxpayers. Therefore, continuous efforts by the government are needed to improve tax education, simplify calculation mechanisms, and strengthen digital- based tax administration systems to ensure a more optimal and effective implementation of Income Tax Article 25.